Bryophyte stable isotope composition, diversity and biomass define tropical montane cloud forest extent. Issue 1895 (23rd January 2019) - Horwath, Aline B.; Royles, Jessica; Tito, Richard; Gudiño, José A.; Salazar Allen, Noris; Farfan-Rios, William; Rapp, Joshua M.; Silman, Miles R.; Malhi, Yadvinder; Swamy, Varun; Latorre Farfan, Jean Paul; Griffiths, Howard
Abstract : Liverworts and mosses are a major component of the epiphyte flora of tropical montane forest ecosystems. Canopy access was used to analyse the distribution and vertical stratification of bryophyte epiphytes within tree crowns at nine forest sites across a 3400 m elevational gradient in Peru, from the Amazonian basin to the high Andes. The stable isotope compositions of bryophyte organic material ( 13 C/ 12 C and 18 O/ 16 O) are associated with surface water diffusive limitations and, along with C/N content, provide a generic index for the extent of cloud immersion. From lowland to cloud forest δ 13 C increased from −33‰ to −27‰, while δ 18 O increased from 16.3‰ to 18.0‰. Epiphytic bryophyte and associated canopy soil biomass in the cloud immersion zone was estimated at up to 45 t dry mass ha −1, and overall water holding capacity was equivalent to a 20 mm precipitation event. The study emphasizes the importance of diverse bryophyte communities in sequestering carbon in threatened habitats, with stable isotope analysis allowing future elevational shifts in the cloud base associated with changes in climate to be tracked.